Experimental parameters affecting the photocatalytic reduction performance of CO2 to methanol: A review. (30th January 2018) - Lais, Abul; Gondal, M.A.; Dastageer, M.A.; Al‐Adel, F.F.
Summary: Photocatalytic conversion of CO2 into value‐added hydrocarbon fuels and/or useful chemical products, using solar energy, has been the focus of active research, owing to its tremendous potential to provide a green fuel (eg, methanol) and simultaneously mitigate global warming by reducing CO2 levels in the atmosphere. CO2 photocatalytic reduction yields various hydrocarbon products. In this paper, we focus on methanol as it is an easily transportable energy‐dense fuel with multifarious applications in the automobile, industrial, and petrochemical sector. The photocatalytic conversion rate of CO2 to methanol depends on 3 factors: the photocatalyst used, photoreactor design, and experimental parameters (or variables). The last factor—experimental parameters—forms the basis of this review paper. These parameters include the reaction temperature, CO2 pressure, solvent used, intensity, wavelength, and duration of the incident light, concentration of organic impurities adsorbed on catalytic surface, addition of hole scavengers, type of reductant used, catalyst loading method, catalyst concentration, and the dissolved oxygen concentration. There have been numerous published works aiming to improve the methanol formation rate by optimizing these experimental parameters. In this paper, we consolidate and review these parameters, and investigate how optimizing them can enhance the photocatalytic conversion rate of CO2 into methanol, thus ushering in the era of a green methanol‐based economy.